Boletus edulis ribonucleic acid – a potent apoptosis inducer in human colon adenocarcinoma cells. Issue 7 (15th June 2016) - Lemieszek, Marta Kinga; Ribeiro, Miguel; Guichard Alves, Helena; Marques, Guilhermina; Nunes, Fernando Milheiro; Rzeski, Wojciech
Abstract : Despite the large popularity of the Boletus edulis mushroom, little is known about its influence on human health and the possibilities of its therapeutic use. Abstract : Despite the large popularity of the Boletus edulis mushroom, little is known about its influence on human health and the possibilities of its therapeutic use. Nevertheless, several reports revealed the usefulness of biopolymers isolated from it in cancer treatment. Our previous studies have shown that B. edulis water soluble biopolymers are not toxic against normal colon epithelial cells (CCD841 CoTr) and at the same concentration range elicited a very prominent antiproliferative effect in colon cancer cells (LS180) which was accompanied with cell cycle arrest in the G0/G1 phase. The purpose of the present study was to verify the proapoptotic properties of a selected fraction from B. edulis – BE3, as well as determine its chemical nature. The BE3 fraction was extracted with hot water and purified by anion-exchange chromatography. Further chemical examinations revealed that BE3 consists mainly of ribonucleic acid (59.1%). The ability of BE3 to induce programmed cell death was examined in human colon cancer cell lines LS180 and HT-29 by measuring caspase activation, DNA fragmentation and expression of BAX, BCL2, TP53 and CDKN1A genes. The sensitivity of colon cancer cells with silenced BAX, TP53 and CDKN1A expression to BE3 treatment was also evaluated. We have demonstrated for the first time that the BE3 fraction is a potent apoptosis inducer in human colon cancer cells. The revealed mechanism of apoptosis triggering was dependent on the presence of functional p53 and consequently was a little different in investigated cell lines. Our results indicated that BE3 stimulated proapoptotic genes BAX (LS180, HT-29), TP53 (LS180) and CDKN1A (HT-29) while at the same time silenced the expression of the key prosurvival gene BCL2 (LS180, HT-29). The obtained results indicate the high therapeutic potential of the BE3 fraction against colon cancer, yet it is necessary to further confirm fraction efficacy and safety in animal and clinical studies.